Optimal Pricing and Investment in Electricity Supply: An essay in applied welfare economics - Turvey, Ralph (London: George Allen & Unwin, 1968)
This essay reveals the optimal investment value in electricity supply in general, not about the particular problems of England and Wales. The only limitation on its generality is that the special problems of hydro-electric power are not discussed. It is aimed both at economists and at those engineers and administrators who are concerned with electricity supply.
Includes bibliographic footnotes and index.
ne 27/04/2018
Loans
Keywords: Electric Utilities; Electric Power-Plants.